Perancangan Node Sensor Nirkabel BLE Bertenaga Baterai menggunakan ESP32 untuk Aplikasi Pertanian Cerdas - Wirawan, Adi Pandu; Nugroho, Happy (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2023)
Increasing the effectiveness and efficiency of agriculture can be done by applying sensor technology, automation, monitoring, and remote control through the Wireless Sensor Network (WSN). One of the technologies used is Bluetooth Low Energy (BLE). The presence of the ESP32's System on Chip (SoC) makes it possible to implement a battery-powered WSN device that is suitable for agricultural purposes when the electrical infrastructure is limited. In this research, a battery-powered BLE sensor node prototype has been created. The node can transmit temperature, humidity, and battery level information. The data sent has been designed based on the Bluetooth Generic Attribute Profile (GATT) standards and specifications. nRF Connect’s application shows that the data sent by the designed node complies with the GATT attributes standard. Testing of temperature and humidity sensor readings has also been carried out with 1% and 2.2% errors respectively. Tests were also carried out on battery-level readings and a 4.2% error was obtained. Through distance testing between nodes, the node can transmit data properly up to 10 meters.